Genetic mechanisms and signaling pathways in autosomal dominant polycystic kidney disease - Harris, Peter C. (American Society for Clinical Investigation, 2014)
Recent advances in defining the genetic mechanisms of disease causation and modification in autosomal dominant polycystic kidney disease (ADPKD) have helped to explain some extreme disease manifestations and other phenotypic variability. Studies of the ADPKD proteins, polycystin-1 and -2, and the development and characterization of animal models that better mimic the human disease, have also helped us to understand pathogenesis and facilitated treatment evaluation. In addition, an improved understanding of aberrant downstream pathways in ADPKD, such as proliferation/secretion-related signaling, energy metabolism, and activated macrophages, in which cAMP and calcium changes may play a role, is leading to the identification of therapeutic targets. Finally, results from recent and ongoing preclinical and clinical trials are greatly improving the prospects for available, effective ADPKD treatments.